2014
DOI: 10.1136/bmj.g7182
|View full text |Cite
|
Sign up to set email alerts
|

Operating theatre time, where does it all go? A prospective observational study

Abstract: Objective To assess the accuracy of surgeons and anaesthetists in predicting the time it will take them to complete an operation or procedure and therefore explain some of the difficulties encountered in operating theatre scheduling.Design Single centre, prospective observational study.Setting Plastic, orthopaedic, and general surgical operating theatres at a level 1 trauma centre serving a population of about 370 000.Participants 92 operating theatre staff including surgical consultants, surgical registrars, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 6 publications
0
11
0
4
Order By: Relevance
“…These factors are difficult, if not impossible, to be incorporated into the preoperative prediction model. For instance, it has been shown by [3] that general surgeons underestimated surgery durations by 31 minutes in average, while anesthesiologists underestimated the durations by 35 minutes (29% and 167% error with respect to predicted durations, respectively). Such underestimation will lead to longer waiting time for patients, e.g., a large variation of waiting time (47±17 mins) over 157 cholecystectomy patients was observed in [4], while it typically requires 25 minutes for patient preparation.…”
mentioning
confidence: 99%
“…These factors are difficult, if not impossible, to be incorporated into the preoperative prediction model. For instance, it has been shown by [3] that general surgeons underestimated surgery durations by 31 minutes in average, while anesthesiologists underestimated the durations by 35 minutes (29% and 167% error with respect to predicted durations, respectively). Such underestimation will lead to longer waiting time for patients, e.g., a large variation of waiting time (47±17 mins) over 157 cholecystectomy patients was observed in [4], while it typically requires 25 minutes for patient preparation.…”
mentioning
confidence: 99%
“…This degree of accuracy was comparable to medical staff (including orthopaedic surgeon) estimation in the global literature, whereby the best estimates of trauma time were within 30% of actual surgical times 16 . Some studies have shown greater accuracy of orthopaedic surgeons in predicting surgical time but these did not include anaesthetic time, which is vital when predicting timing for orthopaedic trauma lists 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Planning is essential for efficient implementation of surgical lists. The variability of orthopaedic trauma, however, makes it extremely difficult to predict workload and capacity 1,2 . The surgical priority of patients can change relatively quickly and some complications can render patients acutely unfit for surgery 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Uno de los procesos más complejo de la cotidianidad, es la toma de decisiones con base a la planificación (Luo, 2018). La planificación resulta esencial para alcanzar procedimientos eficientes (Wang & Yang, 2014;Travis et al, 2014) y con frecuencia, pensar en el logro de resultados deseados donde podrían incluirse multitudes de situaciones y rutas de orientación al menos, desde la evaluación sobre dos criterios: 1 ro ), valor objetivo de las acciones a realizarse y 2 do ), mostrar capacidades para conseguirse (Fisher, 2018).…”
Section: Introductionunclassified